SISTEM PENDUKUNG KEPUTUSAN KELOMPOK PENENTUAN DOSEN PENGAMPU MATA KULIAH DENGAN METODE PROMETHEE DAN BORDA - Heroe Santoso; Raisul Azhar; I Putu Hariyadi; Husain, Husain; Yayan Suganda (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2023)
Lecturers are professional educators and scientists with the main task of teaching, transforming, developing and disseminating science, technology, and art (IPTEKS) through teaching, research and community service. The position of lecturers as professionals serves to increase the dignity of lecturers and develop science and technology to improve the quality of national education. The goal is to implement the national education system and realize the goals of national education. The head of the study program and the dean in determining the lecturers for the courses are still done manually based on the competence of each lecturer and looking at the previous semester's teacher decisions. In this method of determination, of course, the results obtained are still not optimal because there are still some lecturers who do not match the competencies/qualifications of the courses being taught. Based on the problems above, the faculty will think of a better system, namely switching from a manual system to a Group Decision Support System (GDSS). The GDSS method used is the promethee and borda method which is one method of solving decision-making problems in a group. With promethee and borda method, several different opinions or perceptions about a decision can be combined into a group/joint decision. That way, the resulting decisions can be accepted by the group. The system development method uses the waterfall method which consists of several stages, including: data collection stage, analysis stage, design stage, coding stage and testing stage. The conclusion of this study resulted in a Group Decision Support System for determining the lecturers of courses using the borda method. Based on the results of system testing, respondents stated that the system can simplify and speed up the process of determining the course lecturers.